Research techniques for high pressure and high temperature - Ulmer, Gene C. (Estados Unidos | ESTADOS UNIDOS Springer Verlag / New York, 1971)
Table of contents: An introduction to high pressure high temperature technology; Gaseous buffering for the control of oxygen fugacity at on atmosphere; Electrochemical measurements and control of oxygen fagacity and other gaseous fugacities solid electrolyte systems
Sin Especificar
Keywords: Técnicas de investigación | Temperaturas altas